Upaya Penyelesaian Kredit Bermasalah Dalam Penyerahan Oleh Bank Yang Menyangkut Kedua Belah Pihak Pada Masa Pandemi Covid-19 - Alamsyah, M. Albizard Alief; Laksana, I Gusti Ngurah Dharma (Kertha Negara : Journal Ilmu Hukum; Vol 11 No 5 (2023), 2023)
The result of the bank's business debate is the collection and distribution of capital in the form of loans to the public loans. In the face of the COVID-19 pandemic, bank loans were disrupted, resulting in bad credit and payment defaults. This is what keeps people from fulfilling many of their needs, business obligations and promises. I made. Increase default risk. B. Late payment of Loan installments and other payments previously agreed with the bank. This paper is an experimental legal study focused about field research. The research method is a descriptive qualitative method using primary and secondary data. Data collection method used to create this piece is that of interviewing the principal's supervisor. The findings of this thesis study conclude that the underlying cause of bad credit is the pandemic that is affecting business operations and causing defaults by debtors, thus resolving credit disputes with banks. requires a non-judicial method (out-of-court, non-religious method). Dealing with debtors and looking for ways so that the debtor can fulfill his obligations.